(3GdebGhdGJjI hQjGOI GdCYeGds - (3OGSI(B, (3eUWais ((3GdLRGFQs (3OGQ GdHGMK ddWHGYI hGdfTQ hGdJhRjYs, 2022)
(3eONd eaGgjej ddebGhdGJjI h COhGQgG GdeJYOOI, hGdebGQHGJ GdYdejI dJWhQ GdacQ hGdfTGW GdebGhdGJj,cPdc GdJYdje GdebGhdGJj QDjI GSJQGJjLjI, eY GdJacjQ GdebGhdGJj hGdeLJeY HeG ajg ecGfI GdaYd GdebGhdGJj aj GdeLJeY hGdYed GdGLJeGYj, hGdKbGaI GdebGhdGJjI hOhQgG aj JWhjQ GdYed GdebGhdGJj, hCNjQG GdeTQhY GdebGhdGJj eagheg heQGMdg hgjFGJ OYeg(B.s
Keywords: (3GdebGhdGJs